2010
DOI: 10.1080/18811248.2010.9711976
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Process for Sinter-Active U3O8Powders

Abstract: The effect of the oxidation temperature of UO 2 pellets on the powder properties of oxidized U 3 O 8 powders has been investigated. The powder morphology, crystalline size, and BET surface area of recycled U 3 O 8 could be modified by controlling the oxidation temperature of the UO 2 pellets. Recycled U 3 O 8 powder with a high BET surface area and a small particle size could be obtained by lowering the oxidation temperature. It was also found that this low-temperature-oxidized sinter-active U 3 O 8 powder is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Even though the final destiny of the U3O8 powders produced during oxidation treatment of the Dounreay UC pellets is not clear yet, having a powder with higher SSA, using 873 K treatment, could benefit the sintering process of possible recycled fuels in the future. Previous studies by Yang et al [40] on oxidation of UO2 showed that by lowering the temperature from 723 K to 598 K, the U3O8 powder produced had higher SSA and smaller particle size (SSA of 1.50 m 2 g -1 for U3O8 powder oxidised at 598 K and SSA of 0.66 m 2 g -1 for U3O8 powder oxidised at 723 K). Yang et al [40] observed that a finer U3O8 powder was more sinter-active and improved the densification of recycled UO2 pellets compared to high-temperature (723 K) oxidised U3O8 powder [40].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even though the final destiny of the U3O8 powders produced during oxidation treatment of the Dounreay UC pellets is not clear yet, having a powder with higher SSA, using 873 K treatment, could benefit the sintering process of possible recycled fuels in the future. Previous studies by Yang et al [40] on oxidation of UO2 showed that by lowering the temperature from 723 K to 598 K, the U3O8 powder produced had higher SSA and smaller particle size (SSA of 1.50 m 2 g -1 for U3O8 powder oxidised at 598 K and SSA of 0.66 m 2 g -1 for U3O8 powder oxidised at 723 K). Yang et al [40] observed that a finer U3O8 powder was more sinter-active and improved the densification of recycled UO2 pellets compared to high-temperature (723 K) oxidised U3O8 powder [40].…”
Section: Discussionmentioning
confidence: 98%
“…For all temperatures, as soon as oxygen was inserted into the chamber the sample edges cracked and spallation or exfoliation of small particles occurred. After ~2 minutes from oxygen insertion, what is normally referred to as a "popcorn morphology" of the oxide [40], [41] appeared mostly along sample edges (see Figure 6a to e). In samples oxidised at 873 K, the morphology of the oxide resembling U3O8 homogeneously appeared on the entire surface within 5 minutes of oxygen exposure (see Figure 6a, b and c).…”
Section: Fragments Oxidised In a Ht-esemmentioning
confidence: 99%